Effects Of Perceived Risk And Organisational Support On The Relationship Between Hostile Environment And Expatriate Adaptation In Nigeria - Ndagi, Abdullahi (2025)
This research examined the intricacies of nigeria’s hostile environment and how perceived risk as a mediator trigger expatriates’ adaptation. The research framework integrates how organisational support moderates these relationships along expatriate adaptation. Recent world investment report indicates that maladaptation of expatriates has resulted in delays and cancellations of infrastructure projects in developing countries. This is as a result of expatriates not being able to adapt and acquaint with distant cultures in the foreign country. In addition, unstable country’s conditions may constitute monumental losses to multinational organisations as well as clients. Drawing on the anxiety uncertainty management theory, this study examined how terrorism, kidnapping, workplace bullying and culture shock as the antecedents of nigeria’s hostile environment influences adaptation of corporate expatriates. With a sample of 192 expatriates who have lived in nigeria for more than six months, the study employed purposive sampling technique and collected data using electronic survey of online google forms. Pls-sem analyses for direct relationships showed that terrorism does not influence expatriates’ adaptation in both work and non-work domains. Conversely, workplace bullying, culture shock and perceived risk indicated strong negative relationships with expatriate adaptation in both work and non-work domains.